Social Sharing of Emotions and Communal Appraisal as Mediators Between the Intensity of Trauma and Social Well-Being in People Affected by the 27F, 2010 Earthquake in the Biobío Region, Chile - Reyes-Valenzuela, Carlos (Front Psychol, 2021)
The psychosocial impacts of natural disasters are associated with the triggering of negative and positive responses in the affected population; also, such effects are expressed in an individual and collective sphere. This can be seen in several reactions and behaviors that can vary from the development of individual disorders to impacts on interpersonal relationships, cohesion, communication, and participation of the affected communities, among others. The present work addressed the psychosocial impacts of the consequences of natural disasters considering individual effects via the impact of trauma and community effects, through the perception of social well-being, the valuation of the community and the social exchange of emotions. The aim of this study was to assess the relationship between individual reactions (i.e., intensity of trauma) and the evaluation of social and collective circumstances (i.e., social well-being) after the earthquake of 27F 2010 in Chile, through collective-type intervention variables not used in previous studies (i.e., social sharing of emotions and community appraisal). For this purpose, a descriptive, ex post facto correlational and cross-sectional methodology was carried on, with the participation of 487 people affected by the 2010 earthquake, 331 women (68%) and 156 men (32%), between 18 and 58 years old (M = 21.09; SD = 5.45), from the provinces of Ñuble and Biobío, VIII region, Chile. The measurement was carried out 4 years after the earthquake and the results show that greater individual than collective involvements were found, mainly in the coastal zone of the region. The mediation analysis showed that the relationship between the intensity of the trauma and social well-being occurs through a route that considers social sharing of emotions and community appraisal. These results indicate that the overcoming of individual affectations to achieve social well-being occurs when in the immediate post-disaster phases the affected communities activate shared emotional and cognitive processes, which allow them to jointly face subsequent threats and abrupt changes.